Sensitivity of preputial and vaginal exfoliative cytological examination for diagnosis of canine leishmaniosis (Leishmania infantum) - ATHANASIOU (Λ.Β. ΑΘΑΝΑΣΙΟΥ) L. V.; CHATZIS (Μ.Κ. ΧΑΤΖΗΣ) M. K.; GOULETSOU (Π.Γ. ΓKΟΥΛΕΤΣΟΥ) P. G.; SARIDOMICHELAKIS (Μ.Ν. ΣΑΡΙΔΟΜΙΧΕΛΑΚΗΣ) M. N. (Journal of the Hellenic Veterinary Medical Society, 2017)
Aim of the study was to examine sensitivity of preputial and vaginal exfoliative cytological examination as a noninvasive alternative to lymph node, spleen and bone marrow cytology, for detection of Leishmania infantum amastigotes in dogs with leishmaniosis, as, in previous studies, the protozoa have been observed in the penis and prepuce of male dogs and in the vagina of female dogs with leishmaniosis. In total, 20 male and 18 female dogs with confirmed leishmaniosis were included in the study. Three cytology smears were prepared from different sites of the preputial cavity of males and one smear was prepared from the anterior vagina of females. Leishmania amastigotes were not observed in these samples after microscopic examination for 20 min at 1,000× magnification. Therefore, preputial and vaginal exfoliative cytology is not recommended for routine diagnosis of canine leishmaniosis.